Species Diversity Pteridophyta in The Area of The Tourism of Supit Urang Waterfall Pujon Malang Regency - Khairunisa, Khairunisa; Wisanti, Wisanti (LenteraBio : Berkala Ilmiah Biologi, 2023)
Pteridophyta have high biodiversity with a total known worldwide there are 12,000 species. Pteridophyta grows in humid environments such as waterfalls. Diversity is very important to know because the diversity of Pteridophyta will provide an overview of the condition of an ecosystem. The purpose of this study was to analyze the diversity index of Pteridophyta species in the Supit Urang Pujon Waterfall Tourism Area. This type of research is exploratory descriptive research with observation techniques. Exploration was carried out at three stations based on different altitudes, namely station 1 (1200 m asl), station 2 (1300 m asl), and station 3 (1400 m asl). Observations were made to determine the morphological characteristics and abiotic environmental factors. Identification using the book Ferns of Malaya, and Diversity of Ferns from East Java. The resulting data is an inventory of species and families at each station. Diversity data were analyzed using the Shannon-Wiener diversity index (H), taxonomic diversity (?) and dominance diversity (?*). The exploration results revealed 33 species of Pteridophyta from 12 families. Station 1 has 16 species from 8 families, station 2 has 20 species from 9 families and station 3 has 21 species from 10 families. Taxonomic diversity (?) of 33.10-51.81 is included in the medium category and dominance diversity (?*) of 2.83-2.86 is included in the low category. Shannon-Wiener (H) diversity of 3.3 is included in medium category. The diversity of Pteridophyta species obtained shows that conservation efforts need to be made because Pteridophyta are important for the ecosystem.